2020
DOI: 10.1016/j.heliyon.2020.e05242
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of TRC105 and decitabine combination in AML xenografts

Abstract: Acute myeloid leukemia (AML) is an aggressive hematologic malignancy, often characterized by poor prognosis following standard induction therapy. The hypomethylating agent decitabine (DAC) is an alternative treatment for elderly and relapsed/refractory AML patients, yet responses following DAC monotherapy are still modest. The transforming growth factor-β (TGF-β) receptor CD105 (endoglin) is expressed in various hematopoietic malignancies, and high CD105 expression correlates with poor prognosis in AML patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Combination treatment with an endoglin antagonist and VEGF antagonist enhances the inhibition of HUVEC angiogenesis, which overcomes drug resistance to VEGF-neutralizing agents. Combination therapy with TRC105 and decitabine provides a sustained anti-leukemic impact in acute myeloid leukemia (AML) xenografts compared to decitabine alone [ 39 ]. TRC105 enhanced the inhibitory effect of sunitinib on VEGF-VEGFR2-Akt-Creb signaling, indicating a molecular collaboration between TRC105 and Sunitinib [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combination treatment with an endoglin antagonist and VEGF antagonist enhances the inhibition of HUVEC angiogenesis, which overcomes drug resistance to VEGF-neutralizing agents. Combination therapy with TRC105 and decitabine provides a sustained anti-leukemic impact in acute myeloid leukemia (AML) xenografts compared to decitabine alone [ 39 ]. TRC105 enhanced the inhibitory effect of sunitinib on VEGF-VEGFR2-Akt-Creb signaling, indicating a molecular collaboration between TRC105 and Sunitinib [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of epigenetic drugs with other drugs such as etoposide, doxorubicin and bortezomib improves therapeutic potency in assays with various cancer cell lines [ 26 ], and Belinky et al demonstrated improved efficacy in lung cancer following treatment of mice with a combination of decitabine and PBA [ 27 ]. Likewise, the combined use of decitabine with an anti-CD105 therapeutic antibody caused a more durable anti-leukemic effect in a xenograft model of acute myeloid leukemia [ 28 ], and Venetoclax, i.e., an oral inhibitor of BCL-2 combined with decitabine or azacitidine, achieved nearly 70% complete remission in treatment-naive, elderly patients with acute myeloid leukemia [ 29 ].…”
Section: Introductionmentioning
confidence: 99%